Cracking the leadership code : three secrets to building strong leaders - Hunkins, Alain, 1968- (John Wiley & Sons, Inc., 2020)
"The data consistently tells us that today?s leaders are not prepared to lead their employees. Too many leaders don?t understand what it takes for them to succeed. Author Alain Hunkins has extensive experience with training leaders, and he has discovered one common thread in all of these different leaders. They?re keenly focused on what they do. But they?re not so focused on how they do it, especially when it concerns doing it with other people. This narrow vision means that they don?t see how their actions produce or destroy trust within their organization, improve or stifle communication between their employees, and build bridges or walls across hierarchies. Unlocking the Leadership Code is a distillation of the principles and practices Hunkins used and refined over his twenty-plus years working with leaders. This book includes his experiences working with some of the world?s top organizations and provides practical tools that will help others accelerate their learning curve and become the leaders they aspire to be. To thrive in the 21st century economy, organizational leadership needs an upgrade. Unlocking the Leadership Code offers a new operating model, introducing a new perspective, a new framework, and new tools. The book argues that effective leadership focuses on a proactive relationship between leader and follower that through three distinct, but interconnected: Connection, Communication, Collaboration. Weaving together brain science, real-life stories, and a practical toolkit, the book shows readers how to communicate, influence, and persuade others more effectively than ever before"--